1997
DOI: 10.1038/bjc.1997.232
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated serum levels of S100 and survival in metastatic malignant melanoma

Abstract: Summary Current reports suggest serum S100 as a prognostic marker for disease progression in advanced malignant melanoma. In this study, we assessed serum levels of S100 and multiple clinical factors in relation to overall survival in 99 patients with metastatic malignant melanoma seen at our institution between May 1990 and April 1996. For statistical analysis, we used both univariate and multivariate Cox proportional-hazards models. Elevated serum levels of S100 correlated with poor outcome in metastatic mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 17 publications
2
50
1
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]48 In 2 cases, 26,29 the Authors reported survival analysis separately for 2 subpopulations that differed by TNM stage: since these subpopulations were completely independent, we considered them separately (Table I).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]48 In 2 cases, 26,29 the Authors reported survival analysis separately for 2 subpopulations that differed by TNM stage: since these subpopulations were completely independent, we considered them separately (Table I).…”
Section: Characteristics Of Identified Studiesmentioning
confidence: 99%
“…[13][14][15] The prognostic potential of S100B serum levels is supported by many reports in the literature. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Nevertheless, some investigators found no association between S100B detection and patients' survival 26,29 ; moreover, others reported that S100B has a prognostic value at univariate but not multivariate survival analysis, 38 which would rule out the value of this biomarker as a prognostic factor independent of the already established prognostic power of the TNM staging system.…”
mentioning
confidence: 99%
“…So far, only one report has been published which concluded that S100B is unlikely to provide any additional information in a multivariate analysis of stage IV melanoma patients [19]. However, in this study, the chosen cut-off value was 3.0 µg/l [19], which is about 15 times higher than in all other published reports on S100B-IRMA in serum [15, 16, 17, 18].…”
Section: Discussionmentioning
confidence: 75%
“…In recently published studies [15, 16, 17, 18, 19], serum S100B levels were determined in melanoma patients with the aim of using S100B as a clinically relevant marker for metastatic disease. In a report by von Schoultz et al [16], statistically significant associations between the length of survival and serum levels of S100B were presented [16].…”
Section: Introductionmentioning
confidence: 99%
“…24 However, other studies have not found that S100B adds any information to known clinical prognostic parameters on multivariate analysis. 29,30 S100B also has value in monitoring patients during therapy, with increasing levels being correlated with progressive disease and decreasing levels with disease regres-…”
Section: Lactate Dehydrogenasementioning
confidence: 99%